ADVERSE EFFECTS IN THE ORO-MAXILLO-FACIAL TERITORY CAUSED BY CHEMOTHERAPEUTICS USED IN THE TREATMENT OF ONCOLOGICAL PATIENTS. REVIEW - Diana-Cristala Kapp; Cristian Martu; Liliana Pasarin; Ionuţ Luchian; Irina-Georgeta Sufaru; Ioana Sioustis; Silvia Martu; Sorina-Mihaela Solomon (Romanian Dental Association for Education, 2019)
Chemotherapy presents a wide variety of side effects alongside the desired antineoplasic, affecting the entire organism through direct and indirect pathways. Both of these are due to the known effect of chemotherapy agents on cells with a high turn-over rate like marrow cells, mucosal cells, hair follicles. In the oral cavity the side effects that occur are due to both the immunosuppression and direct affection of mucosal cells that line the entire oral cavity. The aim of this review is to offer an update on the data present in literature regarding the side effects of chemotherapy within the oral cavity.